2011
DOI: 10.1039/c0an00751j
|View full text |Cite
|
Sign up to set email alerts
|

A novel baseline-correction method for standard addition based derivative spectra and its application to quantitative analysis of benzo(a)pyrene in vegetable oil samples

Abstract: In the present work, a baseline-correction method based on peak-to-derivative baseline measurement was proposed for the elimination of complex matrix interference that was mainly caused by unknown components and/or background in the analysis of derivative spectra. This novel method was applicable particularly when the matrix interfering components showed a broad spectral band, which was common in practical analysis. The derivative baseline was established by connecting two crossing points of the spectral curve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…A more reliable and feasible route to determine the transition from insulating to semiconducting state is to utilize the first-order derivatives of the light absorbance ( A′ ). Previously the first-order derivatives of absorbance has been used in UV/vis spectroscopy to obtain the maximum absorbance wavelength at A′ = 0, or to eliminate the effect of baseline shifts and baseline tilts which may occur during a spectroscopy observation [16]. However, it is found that the first-order derivatives of absorbance also can be used to determine the insulator-to-semiconductor transition.…”
Section: Resultsmentioning
confidence: 99%
“…A more reliable and feasible route to determine the transition from insulating to semiconducting state is to utilize the first-order derivatives of the light absorbance ( A′ ). Previously the first-order derivatives of absorbance has been used in UV/vis spectroscopy to obtain the maximum absorbance wavelength at A′ = 0, or to eliminate the effect of baseline shifts and baseline tilts which may occur during a spectroscopy observation [16]. However, it is found that the first-order derivatives of absorbance also can be used to determine the insulator-to-semiconductor transition.…”
Section: Resultsmentioning
confidence: 99%
“…The first and second derivatives of Savitzky–Golay were applied to correct the baseline and to improve resolution of the spectral bands . Finally, MSC was used to remove the effects of light scattering caused by non‐homogeneous particle size …”
Section: Methodsmentioning
confidence: 99%
“…In addition, the baseline slope is affected by reflection, temperature, concentration or anomalies of the instrument used. These effects can be minimized through a variety of baseline correction techniques, such as multiplicative scatter correction (MSC) [42], standard normal variate (SNV) [42], and derivative [43], among others [33,44,45].…”
Section: Baseline Correctionmentioning
confidence: 99%